Reactivity of Cu(I) nacnac complexes towards [Cp*Ru(η5-E5)] (E = P, As). (22nd June 2022) - Haimerl, Maria; Scheer, Manfred
Abstract: The reactivity of the nacnac Cu(I) compound [L 2 Cu(MeCN)] (2 ) (L 2 = [{N(C6 H3 Me2 -2, 6)C(Me)}2 CH] - ) towards complexes containing aromatic cyclo -E5 ligands (E = P, As) was investigated. The copper complex was reacted with [Cp*Ru(η 5 -E5 )] (E = P (1a-Ru ), As (1b-Ru )), yielding the heterometallic complexes [(Cp*Ru)(μ, η 5:2 -E5 )(L 2 Cu)] (E = P (3a ), As (3b )). These neutral and molecular complexes represent rare examples of the coordination of group 11 metal complexes to cyclo -En units and are also rare examples of the coordination compounds of 1a-Ru and 1b-Ru . They were fully characterized by crystallographic and spectroscopic methods and compared to related compounds. Graphical Abstract: UF0001